EFFECT OF DEBT TO ASSET RATIO AND DEBT TO EQUITY RATIO ON RETURN ON EQUITY IN MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE SECTOR REGISTERED ON IDX 2017 -2022 - Widy Hastuty Hs; Amin Hou (SEAN Institute, 2023)
Study This aims To know to influence Debt to equity Ratio And Debt Assets Ratio to Return On Equity with the title Influence Debt to Equity Ratio and Debt to Asset Ratio Return On Equity for companies in the food and beverage sector manufacturing companies listed on the IDX for the period 2017 – 2022. Type research used studies quantitative The type of data used researcher is secondary data in the form of quantitative Population in the study This consists of all company manufacturers in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the period 2017 – 2022 i.e. as many as 43 companies. And the sample in research This uses the technique of purposive sampling totaling 10 companies listed on the Indonesia Stock Exchange that meet the characteristics of the For done research. Data analysis techniques in research This uses the regression test multiple and hypothesis testing using SPSS V. 25 software. The results study This is the influence of DAR on ROE obtained 2.505 > 2.001. And have a number significance of 0.006 <0.05. the effect of DER on ROE obtained 2,472 > 2,001. And have a number significant of 0.002 <0.05. Based on the results the can Debt to equity ratio is influential positive and significant to return on equity. kindly simultaneous is known mark F count of 8.402 > F table 3.15 with significant 0.005 <0.05 then H an accepted. It means There is an influence Which positive and significant in a manner together from whole variable free Debt to Asset Ratio and Debt to Equity Ratio to variable bound return on equity.